2019
DOI: 10.3389/fphys.2019.01032
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term High-Altitude Hypoxia and Alpha Adrenoceptor-Dependent Pulmonary Arterial Contractions in Fetal and Adult Sheep

Abstract: Autonomic innervation of the pulmonary vasculature triggers vasomotor contractility predominately through activation of alpha-adrenergic receptors (α-ARs) in the fetal circulation. Long-term hypoxia (LTH) modulates pulmonary vasoconstriction potentially through upregulation of α 1 -AR in the vasculature. Our study aimed to elucidate the role of α-AR in phenylephrine (PE)-induced pulmonary vascular contractility, comparing the effects of LTH in the fetal and adult periods on α-AR subtypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
0
7
1
Order By: Relevance
“…In contrast, no changes were observed in the vascular response to phenylephrine in-between groups. Finally, although sympathetic innervation is upregulated by hypoxia via receptor α- and β-adrenergic receptors (ARs) as shown in vascular circulation, in which adrenoceptors contribute to hypoxic vasoconstriction by hypoxia 47 , our results did not show significant difference in vasoconstriction by phenylephrine. It has been shown that there is a differential regulation in the expression of adrenoceptors in models of intermittent chronic hypoxia, in particular, the increase of the β2 isoform in relation to the β1 in smooth muscle cells of cardiac tissue 48 .…”
Section: Discussioncontrasting
confidence: 60%
“…In contrast, no changes were observed in the vascular response to phenylephrine in-between groups. Finally, although sympathetic innervation is upregulated by hypoxia via receptor α- and β-adrenergic receptors (ARs) as shown in vascular circulation, in which adrenoceptors contribute to hypoxic vasoconstriction by hypoxia 47 , our results did not show significant difference in vasoconstriction by phenylephrine. It has been shown that there is a differential regulation in the expression of adrenoceptors in models of intermittent chronic hypoxia, in particular, the increase of the β2 isoform in relation to the β1 in smooth muscle cells of cardiac tissue 48 .…”
Section: Discussioncontrasting
confidence: 60%
“…PH can affect different regulatory areas in the brain and alter the expression of adrenergic receptors in the heart and arteries. [23][24][25] These changes can lead to a modified function of the autonomic nervous system and increase sympathetic nervous system activity. 8 Long-lasting PH can affect both the central and peripheral control mechanisms mediated by transcriptomic and epigenomic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…8,15 The absence of differences in the BP response to norepinephrine administration between PH and control rats does not exclude the participation of the sympathetic nervous system in their different response to ALAN at the central level because peripherally administered norepinephrine is unable to penetrate the blood-brain barrier. 38 Furthermore, the expression of adrenergic receptors in the heart and blood vessels [23][24][25] can be different and should be further studied.…”
mentioning
confidence: 99%
“…Increased wall thickness of small pulmonary arteries Llanos et al 30 Fetal/neonatal chronic hypoxia Increased pulmonary 5HT and PDE-5. Increased NO vasodilator capacity and wall thickness in small pulmonary arteries Parraguez et al 45 Fetal chronic hypoxia Long-and short-term exposure to high-altitude causes disturbances in maternal ovarian steroidogenesis and negatively affects embryo-fetal growth Moretta et al 47 Fetal chronic hypoxia Gestational hypoxia modulates pulmonary vasoconstriction potentially through upregulation of α1-AR.…”
Section: Referencementioning
confidence: 99%
“…2,17,21,31,34 The sheep has been used as a model that represents an animal not adapted to high altitude, such as the human species. 21,30,[42][43][44][45][46][47][48][49] Pregnant women and their unborn babies from several regions of the world are chronically exposed to the low-oxygen milieu of high-altitude mountains or plateaus. 21,50,51 Pregnancy at high altitude is clearly a potential burden for both mother and fetus.…”
Section: Fetal and Neonatal Cardiovascular Response To Chronic Hypoxiamentioning
confidence: 99%